2019
DOI: 10.1016/j.stem.2019.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Conditioning Enables MHC-Mismatched Hematopoietic Stem Cell Transplants and Organ Graft Tolerance

Abstract: Graphical Abstract Highlights d Six antibodies suppress a mouse's HSCs, T cells, and NK cells in 8 days d Antibody treatment enables HSC transplants without radiation and/or chemotherapy d Transplants can be performed with fully MHC mismatched donors d Following HSC transplants, animals tolerate solid organs from the same donor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 76 publications
0
44
0
1
Order By: Relevance
“…25 Currently, ex vivo HSC gene therapy requires myeloablative chemotherapy to ensure engraftment of gene-modified cells, but alternative nonchemotherapy and nonirradiation approaches aimed at reducing short-and long-term toxicities associated with conditioning warrant further investigation. Early protocols and clinical studies that explored naked antibody-based conditioning for HSCT still required the use of chemotherapy and/or radiation, 26 or application to particular disease states. 27 More recently, preclinical models were used to investigate approaches coupling cytotoxic conjugates, such as saporin, to antibodies targeting either CD45, expressed exclusively on most hematopoietic cells including HSCs, or CD117 (c-Kit), a marker of HSCs and hematopoietic progenitors.…”
Section: Resultsmentioning
confidence: 99%
“…25 Currently, ex vivo HSC gene therapy requires myeloablative chemotherapy to ensure engraftment of gene-modified cells, but alternative nonchemotherapy and nonirradiation approaches aimed at reducing short-and long-term toxicities associated with conditioning warrant further investigation. Early protocols and clinical studies that explored naked antibody-based conditioning for HSCT still required the use of chemotherapy and/or radiation, 26 or application to particular disease states. 27 More recently, preclinical models were used to investigate approaches coupling cytotoxic conjugates, such as saporin, to antibodies targeting either CD45, expressed exclusively on most hematopoietic cells including HSCs, or CD117 (c-Kit), a marker of HSCs and hematopoietic progenitors.…”
Section: Resultsmentioning
confidence: 99%
“…By simultaneously targeting the stem cell compartment and malignant cells, the therapeutic goals of HSCT can hypothetically be achieved with toxicities largely confined to the hematopoietic system. Indeed, recent work in murine 17,18,22,23,25,50 , non-human primates 51,52,53 , and early human trials 54 have demonstrated feasibility and limited toxicities of antibody and ADC-based therapies alongside high efficacy in depleting recipient HSCs and/or malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another novel strategy, developed with CIRM support, represents an evolution of the antibody‐based approaches to clearing niche space that were described above. In this case, a pretreatment comprising six monoclonal antibodies that target and suppress HSCs, CD47, T cells, and NK cells was administered prior to allogenic HSCT in mice . Remarkably, this procedure enabled murine recipients to engraft donor cells with mismatches at half (haploid identical) or all major histocompatibility complex (MHC) genes without conditioning or radiation.…”
Section: Medical and Procedural Risks Of Hsctmentioning
confidence: 99%